Penerapan User Interface Design Pattern untuk Situs Web Katalog Seni Pertunjukan Indonesia - I Nyoman Marcel Mahardika; Purwadi, Joko; Susanto, Budi (Jurnal Terapan Teknologi Informasi, 2023)
Performing arts play a significant role in the cultural diversity of Indonesia. However, there are still few media outlets that publish information related to performing arts in one centralized platform. Based on the described issue, a performing arts website is needed to display information related to performing arts and have a well-designed user interface. In this study, an interface design for a performing arts website is developed by applying user interface design patterns as a solution in the interface design process. To achieve a user-centered design that meets users' expectations, the User-Centered Design (UCD) method is employed in the interface design process. The test results indicate that the interface design has a high level of effectiveness and efficiency, with an effectiveness score of 97.85% and an efficiency score of 96.94%. Additionally, website testing was conducted using the System Usability Scale (SUS) method, which resulted in a usability score of 82.87 for the performing arts website. The obtained results indicate that the performing arts website is well-received and effectively used by users.